Spectrum of Liver Pathology in Autopsy Cases: A Study at Ajmer - Porwal, Vandana; Jain, Deepali; Khandelwal, Shweta; Garg, Seema; Rathi, Aparna (Annals of Pathology and Laboratory Medicine, 2018)
Background : It is a known fact that silent liver diseases are common amongst apparently healthy individuals and are sometimes diagnosed only at autopsy The underlying causes of chronic liver diseases vary in different geographic areas and are based on various factors such as socioeconomic status, life style, diet, local or regional infections, and other endemic diseases. Method : The present study was conducted in the Department of Pathology, J.L.N. Medical College, Ajmer during the period from January 2016 to September 2016 on 200 medico-legal autopsy cases brought to the mortuary Information regarding age, sex, place and previous history of any disease etc., were collected from the records and from the relatives. The liver specimens from these cases were examined grossly as well as microscopically to establish presence of liver diseases. Results: Satisfactory tissue samples for histologic evaluation were available in all the cases with a mean age of 40.78 years. Males predominated the study with a male: female ratio of 4.4: 1. Normal histology was found in 10 (6.84%) cases. Important findings included congestion in 72 (49.21), steatosis in 58 (39.72%), chronic hepatitis in 44 (30.13%), steatohepatitis in 12 (18.21%), cirrhosis in 5 (3.42%) cases, hepatic granulomas in 4 (3.8%) cases. Causes of death were: sudden deaths (35.61%), old diseass (13.69%), murder (20.53%), insecticide spillage (7.53%), Road traffic accident (5.47%), alcohol poisoning (4.79%), head injury (2.70%). Conclusion:. The study was conducted only on specimens collected from the mortuary and may not reflect the actual pattern of liver diseases in the local.